Coronary microvascular disease in chronic Chagas cardiomyopathy including an overview on history, pathology, and other proposed pathogenic mechanisms. - Marcos A Rossi (Public Library of Science (PLoS), 2010)
This review focuses on the short and bewildered history of Brazilian scientist Carlos Chagas's discovery and subsequent developments, the anatomopathological features of chronic Chagas cardiomyopathy (CCC), an overview on the controversies surrounding theories concerning its pathogenesis, and studies that support the microvascular hypothesis to further explain the pathological features and clinical course of CCC. It is our belief that knowledge of this particular and remarkable cardiomyopathy will shed light not only on the microvascular involvement of its pathogenesis, but also on the pathogenetic processes of other cardiomyopathies, which will hopefully provide a better understanding of the various changes that may lead to an end-stage heart disease with similar features. This review is written to celebrate the 100th anniversary of the discovery of Chagas disease.